The interplay of race, socioeconomic status and neighborhood residence upon birth outcomes in a high black infant mortality community - Catherine L. Kothari; Rajib Paul; Ben Dormitorio; Fernando Ospina; Arthur James; Deb Lenz; Kathleen Baker; Amy Curtis; James Wiley (Elsevier, 2016)
This study examined the interrelationship of race and socioeconomic status (SES) upon infant birthweight at the individual and neighborhood levels within a Midwestern US county marked by high Black infant mortality. The study conducted a multi-level analysis utilizing individual birth records and census tract datasets from 2010, linked through a spatial join with ArcGIS 10.0. The maternal population of 2861 Black and White women delivering infants in 2010, residing in 57 census tracts within the county, constituted the study samples. The main outcome was infant birthweight. The predictors, race and SES were dichotomized into Black and White, low-SES and higher-SES, at both the individual and census tract levels. A two-part Bayesian model demonstrated that individual-level race and SES were more influential birthweight predictors than community-level factors. Specifically, Black women had 1.6 higher odds of delivering a low birthweight (LBW) infant than White women, and low-SES women had 1.7 higher odds of delivering a LBW infant than higher-SES women. Moderate support was found for a three-way interaction between individual-level race, SES and community-level race, such that Black women achieved equity with White women (4.0% Black LBW and 4.1% White LBW) when they each had higher-SES and lived in a racially congruous neighborhood (e.g., Black women lived in disproportionately Black neighborhood and White women lived in disproportionately White neighborhood). In sharp contrast, Black women with higher-SES who lived in a racially incongruous neighborhood (e.g., disproportionately White) had the worst outcomes (14.5% LBW). Demonstrating the layered influence of personal and community circumstances upon health, in a community with substantial racial disparities, personal race and SES independently contribute to birth outcomes, while environmental context, specifically neighborhood racial congruity, is associated with mitigated health risk. Keywords: Birth outcomes, Low birthweight, Racial disparity, Race, Socioeconomic status, Income, Neighborhood racial density, Racial congruity, United States